PMMA microfiber loop resonator for humidity sensor - Irawati, Ninik; Abdullah, Tengku Normalini Raja; Rahman, Husna Abdul; Ahmad, Harith; Harun, Sulaiman Wadi (Elsevier, 2017)
A PMMA microfiber loop resonator (PMLR) coated with zinc oxide (ZnO) nanostructure is proposed and demonstrated for the monitoring of relative humidity. The PMLR has a loop diameter of 56 μm and was fabricated using direct drawing technique using a 6 μm diameter PMMA microfiber. The results showed an increase in the sensitivity of the sensor with the additional coating of ZnO nanostructure on the surface of the PMMA fiber. The working mechanism of the device is based on the observed decrement in the transmission of the sensor that was carefully placed in a sealed chamber. As the relative humidity level varies from 20% to 80%, the output power of the PMLR with ZnO nanostructure coating decreases linearly from −9.57 dB m to −20.19 dBm with a maximum sensitivity, linearity and resolution of 0.1746 dBm/%, 94% and 6.17%, respectively. This work is highly beneficial as it combines the high sensitivity obtained by using traditional silica fibers but with the ruggedness and flexibility of PMMA fibers, making them highly suitable for continuous monitoring of relative humidity in compact areas.